2021
DOI: 10.1016/j.parkreldis.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Altered glymphatic system in idiopathic normal pressure hydrocephalus

Abstract: To assess the glymphatic activity in patients with idiopathic normal pressure hydrocephalus (NPH) using the "Diffusion Tensor Image-Analysis aLong the Perivascular Space (DTI-ALPS)" method, and determine the feasibility of non-invasive MRI for the evaluation of the glymphatic function. Methods: Between April 2017 and March 2019, 16 patients diagnosed with NPH and 16 age-and sex-matched controls were included. On 3T DTI-MRI, the diffusivities along x-, y-, and z-axes were measured, and the ALPS-indexa ratio tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
114
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 12 publications
3
114
2
5
Order By: Relevance
“…The DTI-ALPS method is used for evaluating the glymphatic system's function or the interstitial fluid dynamics, and this method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. One of the report showed that results of ALPS method were significantly related to glymphatic clearance function calculated on MRI by intrathecal administration of GBCA [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DTI-ALPS method is used for evaluating the glymphatic system's function or the interstitial fluid dynamics, and this method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. One of the report showed that results of ALPS method were significantly related to glymphatic clearance function calculated on MRI by intrathecal administration of GBCA [28].…”
Section: Discussionmentioning
confidence: 99%
“…The DTI-ALPS method provides ALPS index, which is a ratio of the diffusivity in the direction of the perivascular space and the diffusivity in the direction perpendicular to both major fiber tract and perivascular space, based on a special spatial relationship in the fiber tracts and the perivascular space in the axial imaging plane at the corona radiata [19,20]. Recently, the DTI-ALPS method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. These reports indicated that the ALPS-index is a useful biomarker to evaluate the interstitial fluid dynamics or glymphatic function.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pulsatility in the CSF space is increased in iNPH patients [ 15 , 42 ]. Investigations of the glympathic system in iNPH patients using DTI and MR spectroscopy showed altered function of the glymphatic system, in part shown by an accumulation of macromolecules and a decreased leven of N-acetyl aspartate [ 43 45 ]. Our current findings of early presence of WMH can support the abnormal findings of the glympathic system in iNPH patients and seem to point into this direction for the etiology of iNPH.…”
Section: Discussionmentioning
confidence: 99%
“…More reliable neuroimaging techniques are certainly needed, including noninvasive assessment of the glymphatic system. 4 These advances will likely shed light on the relationship between NPH and subclinical aqueductal stenosis, which, we agree, should be another topic for future research.…”
mentioning
confidence: 77%
“…In addition, this article did not fully address other radiographic parameters as possible diagnostic tools and predictors of shunt responsiveness, such as aqueductal cerebrospinal fluid stroke volume and flow. 3,4 Whether the neuroimaging composite scores such as the NPH Radscale 5 mentioned in the article by Fasano et al can also serve as predictors of shunt responsiveness is worth further exploration in future studies. A discussion about differences, if any, in the clinical manifestation of late-onset aqueductal stenosis and the role of endoscopic third ventriculostomy could have been worthwhile as well.…”
mentioning
confidence: 99%